DEVOTION, KNOWLEDGE AND SERVICE: Gandhi’s Interpretation of the Gita - Sharma, Namarta (Journal of Dharma, 2019)
Human beings are involved in a battle with-in and a battle with-out. They do not comprehend the main motive of their life and clash with one another over petty material gains. Society needs the light of knowledge to end this, and Gandhi addresses it with his interpretation of the Bhagavad Gita (the Gita). The Gita helps human beings to come out of the dilemmas of their life. Gandhi advocates Anasakti (non-attachment) yoga as the way of life to liberate oneself from suffering. This paper focuses on Gandhi’s understanding of the Gita as a treatise on Anasakti yoga, and establishes that only through devotion a human being can attain knowledge and develop Anasakti yoga. A devotee realizes the value of service to the humanity. She/he develops the knowledge of ‘Vasudevam sarvamiti’ (whole universe is a manifestation of God). It is thought that in the journey of realizing the supreme goal of life, one acquires the qualities of devotion, knowledge and service.